Hyaluronan-modified transfersomes based hydrogel for enhanced transdermal delivery of indomethacin - Ming Yuan; Jiangxiu Niu; Qinghan Xiao; Huiyuan Ya; Yansong Zhang; Yanli Fan; Lingmei Li; Xueke Li (Taylor & Francis Group, 2022)
Hyaluronic acid (HA), as a hygroscopic and biocompatible molecule, has displayed unique permeation enhancement in transdermal delivery systems. Hence, indomethacin (IND) was encapsulated in HA-modified transfersomes (IND-HTs) to enhance transdermal IND delivery to reduce adverse effects in this study. The physiochemical properties of IND-HTs were characterized. Results showed that the prepared IND-HTs were spherical and revealed good entrapment efficiency (87.88 ± 2.03%), with a nanometric particle size (221.8 ± 93.34 nm). Then, IND-HTs were further incorporated into a carbopol 940 hydrogel (IND-HTs/Gel) to prolong retention capacity on the skin. The in vitro release and skin permeation experiments of IND-HTs/Gel were carried out with the Franz diffusion cells. It was found that IND-HTs/Gel exhibited sustained drug release, as well as superior drug permeation and flux across the skin. Confocal laser scanning microscopy showed improved penetration of HTs/Gel with a wider distribution and higher fluorescence intensity. The hematoxylin-eosin stained showed that HA improved the transdermal effect by changing the microstructure of skin layers and decreasing skin barrier function. In addition, IND-HTs/Gel showed significant analgesic activity in hot plate test and no potentially hazardous skin irritation. This study indicated that the developed IND-HTs/Gel could be a promising alternative to conventional oral delivery of IND by topical administration.